Peculiarities of leaf-cutter ants (Attini: Acromyrmex y Atta) that make difficult their control - Herrera, Madelen; Valenciaga, Nurys (Cuban Journal of Agricultural Science, 2011)
Leaf-cutter ants provoke intense harms in agriculture, forest, and livestock agroecosystems. Colonies persist and grow despite the innumerable control strategies to which they are subject. Thus, the aim of this review is compiling information and discussing distinctive aspects of anatomy, physiology, social structure, and architecture in their nests, which provide resistance to control measures. The symbiosis between leaf-cutter ants and their fungus gives these insects strong defensive mechanisms. Leaf-cutter ants are provided with spines that serve as means of protection against their natural enemies (natural control). Polymorphism is analyzed as one of the particularities of leaf-cutter ants, as well as the advantages of the specialization in tasks within the ant colony. When nests are destroyed (physical control), ant workers focused their work on re-structuring the tunnels and chambers. When the symbiotic fugus is infected (biological or natural control), the contaminated parts are disinfected, pruned, and isolated. It is concluded that leaf-cutter ants have mechanical and chemical defenses that help them to counterbalance the effect of the control measures and allow them to inhabit the soil, an environment that is heterogeneous and abundant in microorganisms. Exocrine glands and symbiotic bacteria are the main source of antiseptics in leaf-cutter ants, because through them the man-used biologic agents are removed. Studying the adaptation mechanisms of leaf-cutter ants is recommended to attain higher effectiveness in the strategies for their ecological management. Key words: Attini, exocrine glands, symbiosis, control.